Facile Preparation of Silver Halide Nanoparticles as Visible Light Photocatalysts - Linfan Cui; Tifeng Jiao; Qingrui Zhang; Jingxin Zhou; Qiuming Peng (Nanomaterials and Nanotechnology, 2015)
In this study, highly efficient silver halide (AgX)-based photocatalysts were successfully fabricated using a facile and template-free direct-precipitation method. AgX nanoparticles, which included silver chloride (AgCl), silver bromide (AgBr) and silver iodide (AgI), were synthesized using different potassium halides and silver acetate as reactive sources. The size distribution of the AgX nanopar‐ ticles was determined by the reaction time and ratio of the reagents, which were monitored by UV-vis spectra. The as- prepared AgX nanoparticles exhibited different photoca‐ talytic properties. This shows the differences for the photodegradation of methyl orange and Congo red dyes. In addition, the AgCl nanoparticle-based photocatalyst exhibited the best photocatalytic property among all three types of AgX nanoparticles that are discussed in this study. Therefore, it is a good candidate for removing organic pollutants.